Effect of Vitamin D on aldose reductase in Indonesian diabetic polyneuropathy patients : a randomized clinical trial - Fitri, Aida; Sjahrir, Hasan; Bachtiar, Adang; Ichwan, Muhammad (Penerbit Universiti Kebangsaan Malaysia, 2022)
Aldose Reductase (AR) is an important factor in the pathogenesis of several Diabetes Mellitus (DM) complications, including diabetic neuropathy (DN). Vitamin D has a direct effect on the pathogenesis of DN. Aldose reductase inhibition is an important element in the prevention of DM complications. The objective of this paper was to assess the effect of vitamin D on AR in Indonesian diabetic polyneuropathy (DPN) patients. This cohort study was undertaken at Haji Adam Malik General Hospital Medan, North Sumatera, Indonesia. In a double-blind, placebo-controlled, clinical trial, eligible patients were randomized to receive vitamin D 50,000 IU/week or placebo for 10 weeks. The primary end-point was mean changes of nerve conduction velocity (NCV) from baseline and after 10 weeks of supplementation. There was no significant correlation between mean changes of vitamin D and AR levels. There was significant correlation with negative direction and weak strength between mean changes of AR level and NCV of motor Tibial nerve (p<0.05; r=-0.337). There was significant correlation with positive direction and moderate strength between mean changes of vitamin D level and NCV of motor Median and Peroneal nerves, and motor and sensory Ulnar nerves (p<0.001; r=0.438 – 0.527). In conclusion, vitamin D supplementation had no effect on AR level in Indonesian DPN patients. Higher AR level was correlated with decreased NCV of motor Tibial nerve. Vitamin D supplementation improved NCV in DPN.